Sex-Based Medicine Meets Psoriatic Arthritis: Lessons Learned and to Learn - Bragazzi, Nicola Luigi; Bridgewood, Charlie; Watad, Abdulla; Damiani, Giovanni; McGonagle, Dennis (Frontiers in Immunology, 2022)
Humorally associated autoimmune diseases generally show a female predominance whereas ankylosing spondylitis, a disease that overlaps with psoriatic arthritis (PsA), shows a male predominance. The present review ascertains the current knowledge of sex-specific differences related to psoriatic arthritis (PsA), a chronic, inflammatory condition associated with psoriasis. Sex differences may have important implications for clinical research in PsA and in terms of epidemiology (incidence, prevalence, lifetime risk, survival, and mortality), clinical, radiological, and laboratory features, and response to treatment. While nationwide surveys and large-scale databases and registries show no sex-specific differences, varying male/female ratios have been reported, ranging from 0.42 to 2.75 (comparable with those reported for psoriasis vulgaris: ranging from 0.28 to 2.38). This may reflect subtle, complex, nonlinear interactions between the biological make-up of the individual (genetic and epigenetic differences), hormonal components including menopausal status, environmental exposures including skeletal physical stressing, and psychological variables. There exists methodological heterogeneity and paucity of data concerning sex-specific differences, in terms of the specific population studied, study design, and the diagnostic criteria utilized. Harmonizing and reconciling these discrepancies would be of crucial importance in achieving the ambitious goals of personalized/individualized medicine and further standardized meta-data and Big Data could help disentangle and elucidate the precise mechanisms of underlying potential PsA sex-specific differences.